Perancangan Alat Pengemas Vakum Untuk Produk Olahan Jamur Tiram Dalam Rangka Meningkatkan Nilai Jual Dan Masa Pakai - Irwan Iftadi; Wakhid Ahmad Jauhari; Hary Purwoko Atmojo Sung Sumargo (Performa: Media Ilmiah Teknik Industri, 2013)
Vacuum packaging appliance serves to package food products by removing all the air that is in the packaging. The purpose of the vacuum packaging is to make the product to be more durable and long lasting. It can also increase the value of merchantability because the product that is processed oyster mushroom is packaged more cleanly. Nowadays, the mushroom seller usually use an automatic type. Based on the seller experience, the device is difficult to operate. Since the parameters of vacuum pump and temperature sealer must be set before using it, moreover the price of equipment is too expensive. Therefore the required design of the vacuum packaging appliance in accordance with the requirement of the seller. Quality Function Deployment (QFD) is employed to design the vacuum packaging equipment. Then an assessment an assessment of the user's voice level of interest, expectation and satisfaction are conducted subsequently. Furthermore, HOQ is developed by determining technical characteristics, weight and what and how relationship. The main priority in the design seen from the order of the highest weight of the technical characteristics. The results from QFD produce 6 attributes (voice of customer) from the complaints of respondents and 10 technical characteristics. Highest weight of the technical characteristics is "total dimensions scaled and customized tool that is packaged with the product" with a weight of 43.20 or 21.16%. Hence, that technical characteristic must be taken into consideration in designing the vacuum packaging equipment